Dinamika Pertumbuhan Kawasan Permukiman Kota Jambi - Nugroho, Cahyadi; Agustang, Andi; Pertiwi, Nurlita (Jurnal Ilmiah Mandala Education (JIME), 2022)
Urban Growth Dyanamics of Settlement Areas in Jambi City. The development of a city will follow trigger factors such as economy, service centers and population. This research tries to describe the growth of urban areas in Jambi City from 2000 to 2020 which is supported by several driving factors from human activity and movement patterns using time series image data from 2000, 2008, 2016 and 2020. The results show that there is a development in the urban area which leads to the Center Business District (CBD). Based on the growth area, there is an increase in the growth of the urban area which leads to expansion diffusion model with concentric shapes. Urban areas that always sustain growth are centered in the Central Business District: Pasar Jambi District, Jelutung District and Jambi Selatan District.